Project 253-2: Wintering, grazing, and fattening heifers, 1951-52. - Smith, E.F.; Good, D.L.; Cox, R.F. (Kansas Agricultural Experiment Station, 2012)
Forty-five good quality Hereford heifer calves were purchased ill south-central Kansas for use in this test. They were ted silage, prairie hay, 1 pound of protein, and 2 pounds of milo grain per head daily until the test started December 11, 1951. The five lightest heifers were discarded and the 40 remaining were divided into four lots of 10 heifers each. The system of management for each lot follows: Lot 1-Wintered on sorghum silage, prairie hay. 1 pound of cottonseed cake, and 2 pounds of milo grain per head daily, free access to mineral (bonemeal and salt) and salt; grazed on bluestem pasture May 1 to July 15; full-fed in dry lot to choice grade. Lot 2-Wintered on dry bluestem pasture, 2 pounds cottonseed oil meal pellets per head daily, mineral (bonemeal and salt), and free access to salt; grazed on bluestem pasture until July 15; full-fed in dry lot to the choice grade. Lot 3-Wintered on brome pasture supplemented when necessary with protein, free access to mineral (bonemeal and salt) and salt; grazed on brome pasture until July 15; full-fed in dry lot to the choice grade.
Keywords: Beef; Protein; Heifers; Management